Current Steering Digital Analog Converter with Partial Binary Tree Network (PBTN) - Mohd Tafir Mustaffa; Yong Cheng Lim; Choon Yan Teh (Institute of Advanced Engineering and Science, 2017)
DACs are essential devices in many digital systems which require high performance data converters. Thus, shrinking of supply voltage, budget constraints of test times, and rising bandwidth requirement causing DAC architectures to highly relying on matched components to perform data conversions. However, matched components are nearly impossible to fabricate; there are always mismatch errors which causes the difference between the designed and actual component value. Dynamic Element Matching (DEM) is one of the techniques that are commonly used to reduce component mismatch error. This technique is a randomization technique to select one of the appropriate codes for each of the digital input value before entering DAC block. Thus, in this research, a new DEM algorithm is proposed on Current-Steering DAC with Partial Binary Tree Network (PBTN) algorithm that utilizes a lower complexity circuit to produce output signals with less glitches. Simulation results for 6-bit 1-MSB PBTN DAC produces 0.3184LSB of DNL, 0.0062LSB of INL, and a power consumption of 14.13 mW, while using only 126 transmission gates.